Carbon bipolar plate flow channel design: carbon plate fabrication - Lum, Hadrian Jing Yao (Nanyang Technological University, 2022)
As environmental issues arise, people are now opting for an alternative energy source instead of burning fossil fuels. Hence, fuel cells are energy conversion devices that are created as a replacement for energy sources. With fuel cells being the energy replacement source for future generations, it is essential for them to perform to their best capability. As such, engineering research was conducted on the performance of fuel cells. This study was conducted due to the lack of in-depth discussion on how the parameters of the bipolar plates could affect the performance of the fuel cell. A series of research was done to determine how the gas dispersion area within the bipolar plates would affect the performance of the fuel cell. The study was done in three sections, simple case, general case, and general case on both electrodes. It was concluded that the equations could be used to determine the various gas dispersion area percentages upon certain assumptions. However, these equations are only intuitively correct, and it would still require future experimental study for validation. Nevertheless, the preliminary studies reported herein would help guide the design and experiments to be conducted in future.